2013
DOI: 10.1080/09712119.2012.739085
|View full text |Cite
|
Sign up to set email alerts
|

Effects of live yeast supplementation on mid-lactation dairy cows performances, milk composition, rumen digestion and plasma metabolites during hot season

Abstract: Effects of live yeast supplementation on mid-lactation dairy cows performances, milk composition, rumen digestion and plasma metabolites during hot seasonFifty-six Holstein cows (36 multiparous and 20 primiparous), that averaged 145923 days postpartum, were used to investigate the supplementing of live yeast (LY) on productivity during hot summer conditions, from July until August 2010. Cows were fed a control diet with or without 4 g of LY (15 )10 9 CFU/g) per cow daily during a five-week period. Cows were mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
26
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(43 citation statements)
references
References 32 publications
11
26
0
1
Order By: Relevance
“…The effects of LY can be considered positive factors for the growth of anaerobic bacteria and thus for digestion in the rumen, which in turn stimulates voluntary food intake and the nutrient supply to the animals, thereby promoting animal performance [12]. Similar to our results, neither Shwartz et al [33] nor Dehghan-Banadaky et al [9] observed any significant effect of LY supplementation on milk yield in lactating cows under heat stress. In contrast, another study reported that the milk yield and the milk protein yield and percentage increased with supplementation of LY [29].…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…The effects of LY can be considered positive factors for the growth of anaerobic bacteria and thus for digestion in the rumen, which in turn stimulates voluntary food intake and the nutrient supply to the animals, thereby promoting animal performance [12]. Similar to our results, neither Shwartz et al [33] nor Dehghan-Banadaky et al [9] observed any significant effect of LY supplementation on milk yield in lactating cows under heat stress. In contrast, another study reported that the milk yield and the milk protein yield and percentage increased with supplementation of LY [29].…”
Section: Discussionsupporting
confidence: 81%
“…A significant increase [9] and increased trends in plasma glucose concentrations [31] have been previously observed in dairy cows supplemented with LY during hot summer conditions. Miller-Webster et al [22] reported that supplementing diets with yeast culture products increased dry matter digestion, total volatile fatty acid (VFA) production, and propionic acid production in continuous cultures.…”
Section: Discussionmentioning
confidence: 67%
“…Di Contanzo et al (1997) reported an increase in plasma glucose content of dairy cows when niacin was fed during heat stress. Dehghan-Banadaky et al (2013) also reported an increase in plasma glucose content when dairy cows under heat stress were supplemented with live yeast. Cows in heat stress have increased reliance on glucose as an energy source .…”
Section: Discussionmentioning
confidence: 90%
“…While table (8 and 10) showed there are not significant increase between groups and periods of Lymphocyte and granulocyte percentage. However, table (9) showed that the third period in the G3 was significant increase (P≤0.05) in the monocyte percentage compared with first period.…”
Section: Resultsmentioning
confidence: 87%
“…From other hand, yeast improvement the body weight and feed conversion efficiency and carcass traits (8). Several studies have shown beneficial ( 9)." Zinc is a nutritionally essential trace element for animals, as it assumes critical role for ensuring proper feed intake and nutrient utilization, skeletal and growth development, skin and hair integrity, nutrient metabolism, reproduction, and immunity (10; 11; 12; 13).…”
Section: Introductionmentioning
confidence: 99%